Study on the Bearing Mechanism and Stability of Surrounding Rock in Original Roadway Filling and Nonpillar Tunneling. (13th March 2023) - Shi, Wenbao; Chang, Jucai; Li, Yan; Li, Dong; Hu, Ru
Abstract : This study is focused on the problem that with the increase of coal seam mining depth, it is difficult to continuously replace mining due to complex roadway layout and unreasonable stope layout. By taking the mining geological conditions of the 62210 fully mechanized mining face of Xinzhuangzi Coal Mine in Huainan mining area, China, as the background, it explores the stress characteristics of the original roadway filling body as well as the stress distribution and deformation characteristics of roadway surrounding rock in original roadway filling and nonpillar tunneling (ORFNPT) through theoretical analysis and numerical simulation. The following findings are obtained. The required strength for the filling body is primarily determined by two factors, i.e., the span of the hanging roof that lies over the filling body and the width of the filling body. The span of the hanging roof is positively correlated with the required strength of the filling body. However, when the width of the filling body reaches a certain value, its further increase fails to change the required strength of the filling body. Compared with gob-side entry driving with small coal pillars, when the ORFNPT technology is applied to the lower-section roadway, the peak stress position in the solid coal on the lower side of the roadway is closer to the roadway sides, and the filling body is of a much higher stress than the small coal pillars. Besides, the roadway surrounding rock undergoes milder deformation. According to the on-site application and measurement data, the roof-to-floor convergence and side-to-side displacement amounts of the roadway are about 89 mm and 58 mm during tunneling of the 62310 working face, and the two amounts are about 910 and 1, 290 mm during recovery of the 62310 working face, respectively. This tunneling method achieves an excellent roadway control effect.